Growth monitoring and mortality risk in low birthweight infants: a birth cohort study in Burkina Faso - Mwangome, M; Ngari, M; Bahwere, P; Kabore, P; McGrath, M; Berkley, JA (F1000 Research Ltd, 2021)
Background: Wasting and underweight in infancy is an increasingly recognised problem but consensus on optimum assessment is lacking. In particular, there is uncertainty on how to interpret anthropometry among low birth weight (LBW) infants who may be growing normally. This research aimed to determine growth of infants from birth to two months (around age of vaccination) and the mortality risk of underweight LBW infants compared to normal birth weight (NBW) infants at two and six months age.